Pathway to Sustainability through Pragmatic Wisdom - Wai Kian Tan (Philosophies, 2022)
In this era of rapid modernization, technology has changed people’s everyday lives globally but at a heavy price, as evidenced, for example, by the earth’s deteriorating environments. Environmental contamination has induced the adverse impacts of climate change, manifested as natural disasters. According to scientific predictions, if climate change continues at the current rate, irreversible damage to the planet’s ability to sustain life could occur by 2100. This disturbing scenario has prompted a wake-up call for promoting sustainability and initiatives, such as the Sustainable Development Goals formulated by the United Nations, which are aimed at influencing and penetrating every aspect of life. This article discusses the importance of pragmatic wisdom for our earth’s restoration through the achievement of sustainability, which requires a revolution in education. A new educational model, particular within higher education, which extends beyond most of the current educational models for acquiring knowledge, is required to promote pragmatic wisdom. Apart from the acquisition of scientific knowledge, philosophical thinking and critical thinking skills are essential for promoting pragmatic wisdom. In this context, an education that couples liberal arts with natural sciences could be one of the solutions for facilitating the transformation of knowledge into pragmatic wisdom, which can potentially foster sustainability.